Writing history in international criminal trials - Wilson, Richard, 1964-; ebrary, Inc. (Cambridge [England] ; New York : Cambridge University Press, 2011)
"This book uses empirical research on three international criminal tribunals to understand how law and history are combined in the courtroom"--
c
Machine generated contents note: 1. Assessing court histories of mass crimes; 2. What does the 'international' actually mean for international criminal trials?; 3. Contrasting evidence: international and common law approaches to expert testimony; 4. Does history have any legal relevance in international criminal trials?; 5. From monumental history to micro-histories; 6. Exoneration and mitigation in defense histories; 7. Misjudging Rwandan society and history at the international criminal tribunal for Rwanda; 8. Permanent justice: the international criminal court; 9. Conclusion: new directions in international criminal trials.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Crimes against humanity; War crimes; Prosecution; Evidence, Documentary; Political violence -- History; Civil war -- History; War -- History; Electronic books